The steel bonnets the story of the Anglo-Scottish border reivers - Fraser, George MacDonald 1925-2008 (Skyhorse Pub., 2008)
From the thirteenth to the sixteenth centuries, outlaws reigned supreme on the contentious frontier between England and Scotland. Feud and terror, raid and reprisal, were the ordinary stuff of life?and a way of survival. Power was held by the notorious border reivers (the steel bonnets, named for their flashy helmets), who robbed and murdered in the name of family: the famous clans (or grains)?like Elliot, Armstrong, Charlton, and Robson?romanticized by Sir Walter Scott. In The Steel Bonnets, George MacDonald Fraser, author of the bestselling Flashman novels, and himself a borderer, tells the fascinating and bloody story of the reivers, their rise to power as ferocious soldiers of horse, and their surprisingly sudden fall from grace